"Two faces’" of Human Capital and Research and Development Activities: Effects of Related tTechnologies and the Regional Technology Portfolio on Total Factor Productivity in Polish Regions - Cieślik, Andrzej
Opis vplyvu výskumu a vývoja na úroveň technologického rozvoja regionálnej ekonomiky. Skúmanie technologickej ne/prepojenosti na rozvoj inovácií a šírenie technológií.